Expanding treatment options for patients with HER2+ metastatic breast cancer with margetuximab plus chemotherapy: a case report series - Mahtani, Reshma; Harpalani, Natasha; Yan, Fengting; Phiel, Kristen; Kovalenko, Iuliia (Frontiers in Oncology, 2024)
Background Human epidermal growth factor receptor 2 protein (HER2)-positive (+) metastatic breast cancer (MBC) is an aggressive disease and patients often undergo multiple lines of therapy following HER2 targeted therapies. The most recent National Comprehensive Cancer Network (NCCN) guidelines recommend margetuximab plus chemotherapy as fourth-line or later therapy for HER2+/hormone receptor (HR) + or negative (–) MBC. The aim of this case series is to provide information regarding margetuximab utilization in clinical practice as later-line therapy in women with HER2+ MBC. Case summaries Margetuximab plus chemotherapy was used as fourth- or later-line treatment in patients who had received multiple HER2-targeted agents, including trastuzumab, pertuzumab, ado-trastuzumab emtansine, trastuzumab deruxtecan, tucatinib, and neratinib. Patients responded to margetuximab plus chemotherapy with real-world progression-free survival (PFS) of 3, 4, and 7 months. Conclusion Clinical outcomes from three heavily pretreated patients with metastatic HER2+/HR+ MBC demonstrated that margetuximab plus chemotherapy resulted in real-world PFS comparable to that reported in the controlled pivotal clinical trial and support use of this targeted therapy option in appropriately identified patients.